2019
DOI: 10.1039/c9dt01650c
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed curcumin based ruthenium(ii) antimicrobials effective against drug-resistant Staphylococcus aureus

Abstract: Two curcumin conjugated ruthenium(ii) polypyridyl complexes, [Ru(NN)2(cur)](PF6) (1, 2), were systematically exploited for their antimicrobial activity in vitro and in vivo and potential selectivity against multidrug resistant S. aureus strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Betts and Wareham [ 43 ] investigated the activity of curcumin on eight MDR clinical isolates and the antibiotic susceptible A. baumannii ATCC 19606, but a too low concentration of the plant substance did not allow for a precise determination of its antibacterial effect with the MIC > 256 µg/mL. For the same reason, the MICs of curcumin against A. baumannii ATCC BAA-1605 and A. baumannii ATCC 17978 were exhibited to be >64 µg/mL [ 38 ] and >500 µg/mL [ 42 ], respectively. In the next work of the authors cited above [ 31 ], the MICs of curcumin were reported as 512–1024 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Betts and Wareham [ 43 ] investigated the activity of curcumin on eight MDR clinical isolates and the antibiotic susceptible A. baumannii ATCC 19606, but a too low concentration of the plant substance did not allow for a precise determination of its antibacterial effect with the MIC > 256 µg/mL. For the same reason, the MICs of curcumin against A. baumannii ATCC BAA-1605 and A. baumannii ATCC 17978 were exhibited to be >64 µg/mL [ 38 ] and >500 µg/mL [ 42 ], respectively. In the next work of the authors cited above [ 31 ], the MICs of curcumin were reported as 512–1024 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The MICs of curcumin against P. aeruginosa PAO1 were determined as 30–512 µg/mL [ 27 , 31 , 57 , 59 ]. For P. aeruginosa ATCC 27853 it was 73.7–512 µg/mL [ 31 , 34 , 58 ], but some authors reported the MICs values as >64 µg/mL [ 38 ], >128 µg/mL [ 33 ], or >375 µg/mL [ 44 ]. In turn, our studies did not show significant activity of curcumin on this strain with a MIC of 5000 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, the compounds showed good MIC values (0.6-0.7 µM, comparable to gentamicin) against MRSA, they were less effective against E. coli and nearly inactive against P. aeruginosa. More recently, Srivastava et al reported ruthenium(II) polypyridyl complexes [97] coordinated to curcumin, [Ru(NN) 2 (cur)](PF 6 ) [NN = bpy, phen], (30, Figure 7) and tested them against a panel of ESKAPE pathogens, including the drug resistant S. aureus ATCC. The results revealed a good inhibitory effect of the complexes against the latter pathogen and a remarkably high selectivity index (MIC = 1 µg/mL vs 0.25 for levofloxacin, SI = 80).…”
Section: Ruthenium Complexesmentioning
confidence: 99%